1987
DOI: 10.1159/000199476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cisapride on Gastric Emptying and Heal Transit Time of Balanced Liquid Meal in Healthy Subjects

Abstract: Cisapride is a new prokinetic gastrointestinal agent which has been shown to be able to increase gastric emptying and intestinal transit time in experimental animals and in patients with preexisting motility alterations. Up to now, however, clinical research evaluating the activity of the drug in healthy subjects is very limited. We have therefore undertaken a placebo-controlled study to simultaneously investigate the effect of cisapride (20 mg p.o.) on gastric emptying and intestinal transit time of a balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Our findings are also in accordance with those of others (Horowitz et al, 1987) who found no significant change in oesophageal transit after cisapride administration in patients with systemic sclerosis. The increase in the number of fundic gastric contractions after cisapride administration in our patients is consistent with the findings of most studies which demonstrated that cisapride shortens gastric emptying of liquids and solids in healthy subjects, or patients with delayed gastric emptying of idiopathic, diabetic, or postsurgical origin (Feldman & Smith, 1987;Jian et al, 1985;Lazzaroni et al, 1987;Miiller-Lissner et al, 1986), or patients with systemic sclerosis (Horowitz et al, 1987).…”
Section: Resultssupporting
confidence: 91%
“…Our findings are also in accordance with those of others (Horowitz et al, 1987) who found no significant change in oesophageal transit after cisapride administration in patients with systemic sclerosis. The increase in the number of fundic gastric contractions after cisapride administration in our patients is consistent with the findings of most studies which demonstrated that cisapride shortens gastric emptying of liquids and solids in healthy subjects, or patients with delayed gastric emptying of idiopathic, diabetic, or postsurgical origin (Feldman & Smith, 1987;Jian et al, 1985;Lazzaroni et al, 1987;Miiller-Lissner et al, 1986), or patients with systemic sclerosis (Horowitz et al, 1987).…”
Section: Resultssupporting
confidence: 91%
“…In man the prokinetic agents metoclopramide (Behar & Ramsby, 1978) and cisapride (Lazzaroni, Sangaletti & Porro, 1987) accelerate gastric emptying, even in subjects with a normal rate of emptying, suggesting that the normal rate of emptying is not the maximum rate, i.e. it is to some extent inhibited (Johnson, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, ultrasonography showed the effectiveness of cisapride administered intravenouslyY In five studies of gastric emptying rate after the oral administration of cisapride, the results were conflicting. Lazzaroni et al, 25 Madsen, 4 and Van Wyk et al? 5 reported accelerated gastric emptying, whereas Edwards et al?…”
Section: Discussionmentioning
confidence: 99%